2019
DOI: 10.1002/ijc.32019
|View full text |Cite
|
Sign up to set email alerts
|

Large scale in vivo micro‐RNA loss of function screen identified miR‐29a, miR‐100 and miR‐155 as modulators of radioresistance and tumor‐stroma communication

Abstract: Micro RNAs (miR) are master regulators of cellular transcriptome. We aimed to investigate the role of miR regulation on tumor radiosensitivity and development of local tumor recurrence by a novel large‐scale in vivo loss of function screen. For stable miR silencing, human A431 tumor cells were transduced with lentiviral constructs against 170 validated human miR (miRzip library). Fractionated radiotherapy (5x6Gy) was applied to A431 miRzip library growing s.c. in NCr nude mice. Enrichment of miRZip and miR exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Targeting NKG2D ligands and/or blocking PD-1/PD-L1 interactions (checkpoint inhibitors) have been the subject of clinical research and application [55] , [56] . Since alterations in the miR-155/NOS2/NO signaling pathway have been reported to attenuate the immune suppressive tumor microenvironment [31] , [57] , [58] , [59] , we hypothesized that endogenous H 2 S may modulate the immunogenic profile of BC cells. Tumor cells tend to down-regulate NKG2D ligands through intracellular retention and/or extracellular shedding to evade NKG2D receptor-mediated NK cell killing.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting NKG2D ligands and/or blocking PD-1/PD-L1 interactions (checkpoint inhibitors) have been the subject of clinical research and application [55] , [56] . Since alterations in the miR-155/NOS2/NO signaling pathway have been reported to attenuate the immune suppressive tumor microenvironment [31] , [57] , [58] , [59] , we hypothesized that endogenous H 2 S may modulate the immunogenic profile of BC cells. Tumor cells tend to down-regulate NKG2D ligands through intracellular retention and/or extracellular shedding to evade NKG2D receptor-mediated NK cell killing.…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer, miR-29a was verified to enhance radioresistance via activating the PI3K/Akt pathway [24]. However, another large-scale in vivo loss of function screen identified miR-29a as a modulator of radiosensitivity, since loss of miR-29a led to enhanced clonogenic survival and reduced apoptosis in irradiated tumor cells [25]. In the present study we established a radioresistant CNE-2R sub-cell line following standard procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that CASC2 could serve as a competing endogenous RNA (ceRNA) or miRNA sponge in the development of cancers [ 12 , 19 ]. Accruing reports demonstrated that miR-155 is an oncogenic miRNA involved in drug resistance and radioresistance in human cancers [ 20 22 ]. Furthermore, it is suggested that miR-155 expression was increased in papillary thyroid carcinoma and its overexpression promoted cell proliferation by regulating adenomatous polyposis coli and Wnt/ β -catenin signaling [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%